(untitled) (Al-Aasar, 2025)
This study explores the integration of trauma-sensitive pedagogical practices within English Language Teaching (ELT) for undergraduate students in Lahore, Pakistan. It investigates how these practices impact Second Language Acquisition (SLA), focusing on cognitive, emotional, and linguistic outcomes. The research employs a mixed-methods approach, combining quantitative assessments, qualitative interviews, and classroom observations to evaluate the effectiveness of trauma-sensitive interventions. The findings reveal significant improvements in language proficiency, classroom engagement, and emotional resilience among trauma-affected learners. Quantitative data demonstrate enhanced performance in listening, speaking, reading, and writing, while qualitative insights underscore the importance of emotional safety, personalized feedback, and culturally inclusive materials in fostering a supportive learning environment. Key practices such as mindfulness activities, scaffolding, and collaborative learning were instrumental in achieving these outcomes. This study contributes to the growing field of trauma-informed education by bridging the gap between psycholinguistics and ELT. It provides actionable recommendations for educators, curriculum designers, and policymakers to implement trauma-sensitive strategies that enhance both linguistic and emotional development. By prioritizing empathy, inclusivity, and resilience, this research advocates for systemic changes in educational practices, ensuring equitable opportunities for all learners.